Risk of Diffuse Infiltrative Lymphocytosis Syndrome in HIV-Infected Patients: A Nationwide Population-Based Cohort Study. (1st October 2018) - Chen, Marcelo; Yen, Yung-Feng; Lan, Yu-Ching; Jen, I-An; Chuang, Pei-Hung; Lee, Chun-Yuan; Lee, Yun; Lin, Yu-An; Arthur Chen, Yi-Ming
Abstract : Objective: Diffuse infiltrative lymphocytosis syndrome (DILS) is the term used for sicca syndrome in HIV patients and has similar clinical manifestations as Sjögren syndrome. In this nationwide population-based study, we aimed to determine the association between HIV infection and DILS in the Taiwanese population. Methods: The National Health Insurance Research Database was searched for cases of DILS in HIV-infected individuals diagnosed between January 1, 2000, and December 31, 2012. The incidence of DILS and the factors associated with DILS in people living with HIV/AIDS (PLWHA) were determined. Results: A total of 20, 364 PLWHA were followed, and 57 (0.28%) individuals had new-onset DILS. The incidence rate of DILS in PLWHA was 0.56/1000 person-years. One (0.11%) female HIV patient with highly active antiretroviral therapy (HAART) and 24 (2.99%) without HAART had incident DILS, whereas 22 (0.17%) male HIV patients with HAART and 10 (0.17%) without HAART had incident DILS. Hypertension increased the risk of incident DILS. HAART decreased the risk of DILS, but this relationship somewhat attenuated in an adjusted model. None of the patients taking emtricitabine, raltegravir, darunavir, enfuvirtide, or tipranavir developed DILS. Lopinavir was associated with a decreased risk of DILS (adjusted hazard ratio = 0.10, 95% confidence interval: 0.01 to 0.84), whereas zalcitabine was associated with an increased risk of DILS (adjusted hazard ratio = 13.7, 95% confidence interval: 2.18 to 85.9). Conclusions: DILS is a rare disease found in PLWHA. Hypertension is a risk factor for incident DILS, and HAART could affect the pathogenesis of DILS. Zalcitabine was the only antiretroviral agent found to increase the risk of DILS.